What drives eco-innovations? - Jaensch, Marius (2014)

(untitled)
This paper investigates the main determinants of eco-innovation for small and medium sized enterprises (SMEs) in the European Union. This topic, which holds considerable relevance for policy makers and their quest for sustainable economic growth, is approached from a theoretical and empirical premise in this paper. Firstly, an extensive literature review ensures the inclusion of all important determinants, which can be grouped into demand-side, supply-side and regulatory factors. In the second stage, an empirical strategy is devised, where ultimately a (1) logistic regression and (2) multinomial logistic regression are rendered as the ideal choices. The employment of two models ensures an extensive overview how these factors influence a firm’s probability to engage in eco-innovation, where particularly the second model provides valuable insights. The multinomial model, through simultaneously running three different regressions, allows deciphering how the influences of the factors may differ at high, medium, and low levels of investments into eco-innovation. The subsequent findings reveal that supply-side factors, namely material and energy prices, and demand-side factors, specifically market share, enhance a firm's probability to engage in eco-innovation at the medium investment level. Interestingly, regulatory factors, namely 'access to subsidies and fiscal incentives' negatively influences a firm's chances to perform eco-innovation at all three investment levels. Furthermore, the control variables, such as a firm's size, industry sector and its country of origin are highly influential through all three investment levels.